Antioxidant Effects Of Cosmos Caudatus, Polygonum Minus And Murraya Koenigii In Spent Hen Burger - Huda-Faujan, N.,; Noriham, A.; Norrakiah, A.S.; Babji, A.S. (Faculty of Veterinar, Universiti Putra Malaysia, 2024)
This study was conducted on three types of plant water extracts namely ulam raja (Cosmos cadatus), kesum (Polygonurn minus) and curry leaves (Murmya koenigii) to observe their antioxidant effects in spent hen burger during three months of frozen storage (-18°C).The antioxidant effects of plants extract were compared with synthetic antioxidants, BHA and BNT at 200 ppm. The analysis carried out on the burger fomulations were peroxide value (PV) and thiobarbituric acid (TBA) test. Results showed the formulations with plant extracts and synthetic antioxidants had significantly lower PV and TBA values (P<0.05) compared to the control. Among the plant extracts, formulation with Cosmos caudatus showed the lowest PV while formulation with BHT showed the lowest TBA value. This indicates that plants extract possessed strong antioxidative power and may be a potent source of natural antioxidant in foods especially in meat and poultry products.